BUDAYA INSTANT DALAM BERKREASI (PRAKARYA) DI SMAN 2 PEKANBARU - Tina Ria; Swis Tantoro (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2014)
Instant culture is practical culture in make prakarya. Instant culture thatpurposed in this research is student that not work prakarya task result howeverpay sartorial to work prakarya task embroidery application namely sewing createstablecloth. If student not creative, so student will be unable to work prakarya taskhimself. Creativity is expression or expression from uniqueness individual ininteraction with the environment that reflect originality from individual. Wayteacher in motivate student so that guilty of no insta culture is by providingdirection and support in student that they able to work prakarya task their own.Effort teacher in improving creativity student are by ppreciate student workresult, grown selfconfidence in student that they able to make prakarya own handcreation result.Purpose from this research is to know student that mak instant culture increating make prakarya. Indoor location this research s SMA Negeri 2Pekanbaru. That enacted by informant in this research is XI student class IPSmajor 5 people and 1 art teacher person. This data col ted next analyzed byDeskriptif Kualitatif. Factors that are impacted stude in make instant culturenamely internal factors and external factor. Thereby inferential that student hatmake instant culture is student that not creative and ask teacher is educate anddirect student so that able to train creativity so that student able to work prakaryatask their own.Keyword: Instant Culture, Prakarya, Creativity, SMA Negeri 2 Pekan aru